The Role of Global Positioning Systems in Modern Navigation and Geospatial Data Analysis - Gupta, Kajal (Journal of Advanced Research in Geo Sciences & Remote Sensing; Vol 12 No 1&2 (2025): Journal of Advanced Research in Geo Sciences & Remote Sensing, 2025)
Global Positioning Systems (GPS) have revolutionized the fields of navigation and geospatial data analysis, becoming an essential tool across a range of industries. Initially developed for military purposes, GPS has evolved to support commercial and civilian applications, including automotive navigation, mobile mapping, environmental monitoring, and urban planning. This review explores the key components of GPS technology, its diverse applications, and its role in modern geospatial data analysis. The article highlights advancements such as Real-Time Kinematic (RTK) GPS, Differential GPS (DGPS), and the integration of GPS with other geospatial technologies like Geographic Information Systems (GIS). Despite its widespread adoption, GPS faces challenges such as signal interference, atmospheric errors, and security vulnerabilities. The article also discusses future trends in GPS technology, including its integration with Global Navigation Satellite Systems (GNSS), autonomous vehicles, and smart city infrastructure. As GPS continues to improve in terms of accuracy, reliability, and integration with other technologies, it remains a critical tool for decision-making and spatial analysis in the digital age.